Sociodemographic disparities in incidence rates of advanced and low-risk prostate cancer as a proxy for diagnostic activity - Ulf Strömberg; Carl Bonander; Hans Garmo; Mats Lambe; Pär Stattin; Ola Bratt (Acta Oncologica)
Background: Inequity in prostate cancer detection can be assessed by relating the diagnostic intensity to the incidence rate of advanced disease in different population groups, according to factors such as socioeconomic status or ethnicity.